Answer :

Now in the above quadratic equation the coefficient of x^{2} is 4. Let us make it unity by dividing the entire quadratic equation by 4.

x^{2} + √3x + 3/4 = 0

x^{2} + √3x = -3/4

Now by taking half of the coefficient of x and then squaring it and adding on both LHS and RHS sides.

Coefficient of x = √3

Half of √3= √3/2

Squaring the half of √3= 3/4

Now the LHS term is a perfect square and can be expressed in the form of (a-b) ^{2} = a^{2} – 2ab + b^{2} where a = x and b = √3/2

On simplifying both RHS and LHS we get an equation of following form,

(x ± A)^{2} = k^{2}

Here RHS term is zero which implies that the roots of the quadratic equation are real and equal.

Taking square root of both sides,

Rate this question :

If u(x) = (x – 1)Rajasthan Board Mathematics

Find the lowest cRajasthan Board Mathematics

Solve the followiRajasthan Board Mathematics

Solve the followiRajasthan Board Mathematics

The area of a recRajasthan Board Mathematics

The LCM and HCF oRajasthan Board Mathematics

If α and β are thRajasthan Board Mathematics

Find the zeroes oRajasthan Board Mathematics

Write ShridharachRajasthan Board Mathematics

Solve the followiRajasthan Board Mathematics